2019
DOI: 10.4103/sja.sja_747_18
|View full text |Cite
|
Sign up to set email alerts
|

Quality of recovery in elderly patients with postoperative delirium

Abstract: Background:Our study aimed to evaluate quality of recovery in elderly patients with postoperative delirium (POD).Subjects and Methods:An observational prospective study was conducted. Patients aged >60 submitted to elective surgery and admitted to Post Anesthesia Care Unit (PACU) in a tertiary hospital from May to July 2017 were included. POD was evaluated with the Nursing Delirium Screening Scale (NuDESC). Quality of recovery-15 (QoR-15) was used before (T0) and 24 h (T24) after surgery to assess quality of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…159,174 POD further impacted on ICU length of stay (LoS) in cardiac surgery patients [175][176][177][178][179] (Fig. 10 the corresponding Funnel plots is Supplement Figure S13, http://links.lww.com/EJA/A851) and hospital LoS for both cardiac and noncardiac surgical patients 167,168,174,[180][181][182][183][184][185][186][187][188][189] (Figs. 11 and 12, the corresponding Funnel plots are Supplement Figure S14, http://links.…”
Section: Discussionmentioning
confidence: 99%
“…159,174 POD further impacted on ICU length of stay (LoS) in cardiac surgery patients [175][176][177][178][179] (Fig. 10 the corresponding Funnel plots is Supplement Figure S13, http://links.lww.com/EJA/A851) and hospital LoS for both cardiac and noncardiac surgical patients 167,168,174,[180][181][182][183][184][185][186][187][188][189] (Figs. 11 and 12, the corresponding Funnel plots are Supplement Figure S14, http://links.…”
Section: Discussionmentioning
confidence: 99%
“…Length of stay (LOS) has been shown to be longer in the elderly who undergo surgery. There is a positive correlation with LOS and delirium in aged patient [65,66]. In a study highlighting the incidence of delirium in the elderly, it was found that patients with advanced age had a higher rate of post-operative delirium (POD) and postoperative cognitive dysfunction (POCD) [67,68].…”
Section: Post-operative Assessmentmentioning
confidence: 99%
“…Moreover, Cristelo et al . [ 10 ] observed in their study that elderly patients had inadequate early postoperative recovery due to a low Richmond Agitation and Sedation Scale (RASS) measured until 15 minutes postoperatively. In addition, elderly patients exhibit poorer psychomotor recovery postoperatively.…”
Section: The Trajectory Of Recovery From Anesthesia In the Elderlymentioning
confidence: 99%